Microstructure and plastic anisotropy of fine grained AZ31 magnesium alloy fabricated by differential speed rolling at 473 and 573 K. (May 2015) - Kaseem, M.; Yang, H. W.; Hamad, K.; Kim, Y. G.; Park, B. H.; Ko, Y. G.
<x content-type="archive" xml:space="preserve">Abstract</x> Differential speed rolling (DSR) was used to deform AZ31 Mg alloy samples at the two rolling temperatures of 473 and 573 K so as to investigate the effects of temperature on the microstructure and plastic anisotropy. The anisotropies in the mechanical properties of the deformed samples were examined by tension tests with respect to three directions (0°, 45°, and 90°) from the DSR deformation direction. A homogeneous and equiaxed microstructure with a mean grain size of ∼14 μm was achieved after DSR deformation at 573 K. Thus, anisotropic behaviour in the mechanical properties was mostly observed in the samples processed by DSR at 473 K. The maximum strength was observed in the 90° direction, and the elongation in the 45° direction was higher than those in other directions. A good combination of high elongation and strength together with the homogenous microstructure was attained on the sample deformed at 573 K.